1998
DOI: 10.1080/00913367.1998.10673544
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotypes in Advertising on Children's Television in the 1990s: A Cross-National Analysis

Abstract: Using content analysis, the author examined sex role stereotyping in television commercials aimed at children in the United States and Australia. The goals of the study were to: (1) provide current data on level and content ofgender stereotyping, (2) compare levels ofstereotyping in two countries, and (3) assess stereotyping olsell-presentational behaviors. Results are consistent with those ofpreuious research in that boys were depicted as being more knowledgeable, active, aggressive, and instrumental than gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
2
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 29 publications
5
140
2
7
Order By: Relevance
“…Our results are consistent with content analyses on the depiction of sex-role stereotypes in commercials, which have often found that advertisers use highly stereotypical means to attract the attention of boys and girls (Allan and Coltrane, 1996;Browne, 1998;Chandler and Griffiths, 2000). Some of these researchers have raised the concern that television advertising imposes or reinforces traditional gender stereotypes.…”
Section: Appeals In Different Product Categoriessupporting
confidence: 80%
“…Our results are consistent with content analyses on the depiction of sex-role stereotypes in commercials, which have often found that advertisers use highly stereotypical means to attract the attention of boys and girls (Allan and Coltrane, 1996;Browne, 1998;Chandler and Griffiths, 2000). Some of these researchers have raised the concern that television advertising imposes or reinforces traditional gender stereotypes.…”
Section: Appeals In Different Product Categoriessupporting
confidence: 80%
“…Gender stereotypes are general beliefs about sexlinked traits and roles, psychological characteristics, and behaviors describing women and men (Browne, 1998). Gender theory has facilitated the discussion of the social and ethical implications of advertising associated with communication of female role stereotypes.…”
Section: Background To Female Role Stereotypesmentioning
confidence: 99%
“…In particular, gender stereotypes can be defined as general beliefs about how normal women and men should think and behave in various social situations (Browne 1998). Researchers have investigated the depiction of women and men in advertising for decades because of the unintended consequences of such images in society (Browne 1998;Courtney and Whipple 1974).…”
Section: Introductionmentioning
confidence: 99%